Advanced adjustable sensor for multi-signal analysis via construction of co-continuous dual-sensing networks. (10th November 2022) - Gao, Tianyuan; Jia, Shunheng; Wang, Jin; Cai, Yu; Zhang, Huanhuan; Jiang, Haowei; Huang, Zhao-xia; Qu, Jin-ping
Abstract: Multifunctional sensors (MFS) have broad prospects in fields such as healthcare and environmental monitoring, which should integrate multi-signal detection. But the signal crosstalk problem limits the functional expansion of sensors, which is an urgent problem that few people have completely solved. We firstly propose to combine two matrices with different sensing function in a co-continuous network as a composite of ''water channel'' and elastic skeleton, to achieve the non-interfering integration of different sensing capabilities in multifunctional sensor. Then, through the study of multi-response law, a mathematical model is innovatively proposed to analyze the synthetic response signals and solve for monitoring signals. From the results, the MFS can maintain excellent mechanical properties while producing superior responses to the triple factors of temperature, humidity and mechanical stimuli. The mathematical model can accurately describe the synergistic effects of temperature and humidity, and the theoretical results are in good agreement with the actual results, which demonstrates the effectiveness of this strategy for discriminating multi-signal responses. Thus, the simple and effective fabricating concept and method for sensors are proposed with the construction of "water channel", which can effectively distinguish temperature and humidity responses through two-phase co-continuous networks with different independent function and a mathematical model. Graphical abstract: Image 1